Worker matching and firm value - Espen R. Moen; Eran Yashiv (Institute for the Study of Labor (IZA), 2012)
This paper studies the value of firms and their hiring and firing decisions in an environment where the productivity of the workers depends on how well they match with their co-workers and the firm acts as a coordinating device. Match quality derives from a production technology whereby workers are randomly located on the Salop circle, and depends negatively on the distance between the workers. It is shown that a worker's contribution in a given firm changes over time in a nontrivial way as co-workers are replaced with new workers. The paper derives optimal hiring and replacement policies, including an optimal stopping rule, and characterizes the resulting equilibrium in terms of employment, wages and distribution of firm values. The paper stresses the role of horizontal differences in worker productivity, as opposed to vertical, assortative matching issues. Simulations of the model show the dynamics of worker replacement policy, the resulting firm value and age distributions, and the connections between them.
Keywords: E23; J62; J63; 330; firm value; complementarity; worker value; Salop circle; hiring; firing; match quality; optimal stopping; Arbeitsnachfrage; Personalmanagement; Matching; Arbeitsproduktivität; Komplementärgut; Suchtheorie; Unternehmenswert; Theorie